(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
Today power remains one of the most effective means of modern world politics. With the concept power is related one of the central problems of international relations – the problem of war and peace, the problem of conflict and its resolution, the issue of security. On the basis of the “power” the actors are judged on mutual opportunities, make plans of their interaction, make decisions, assess the degree of stability of the international system. Category of “power” plays a significant methodological role in the science of international relations. “Power” is an important instrument of their scientific analysis: the significance of “power factor” there have been discussions between the various scientific and theoretical schools. Power a criterion of diverse models of the system of international relations. In practice this means that the various states are used to take advantage of the different models with «hard» or «soft» power.